(untitled) (Journal of Advanced Research in Social Sciences, 2020)
Anchored on the constructivist and social development theory, this study aimed to enhance the chemistry achievement of students in terms of the comprehension, application, and analysis cognitive levels. It also determined the specific factors in the constructivist approach that contributed significantly to students’ achievement and attitude. It employed quasi-experimental method, specifically the pretest – posttest two group design, utilizing both quantitative and qualitative techniques in collecting and analyzing the data. The use of the constructivist approach significantly enhanced the comprehension, application, and analysis cognitive skills. The group exposed to the constructivist approach performed better than the group exposed to the traditional teaching method. The constructivist strategies and students’ involvement have significant correlation on students’ achievement and attitude. Educators should develop students’ higher thinking skills using the constructivist approach in various disciplines. Some designed activities could be given after class hours, as project or assignment, to continue the processing of skill development.